Fragmentation of global law: a cognitive suggestion on how to lead with miraculous normative paralell universes - Dias da Silva, Emílio Mendonça; Tura, Marco Antônio Ribeiro (Revista da Faculdade de Direito da Universidade Federal da Bahia, 2020)
This paper investigates the cognitive challenges that global law is possibly facing in postmodern context. It addresses questions relating to the acceleration of social life and the propensity that all dimensions of law, such as national orders, international law, regional law and so on, have to abrupt changes and transformations in the globalized world. The decisionism behind the abrupt deformation of consecrated policies not always ensure legal coherence; it is likely to promote normative parallel universes. Such permanent decisionism is held, in this paper, as miracles, in a reference to Schimitt’s work. For leading with such questions, it is sustained that there is an emergent cognitive paradigm, which is appropriated to avoid knowledge compartmentalization and to avert legal fragmentation, or at least to empower people to have a position over the miraculous measures. It seeks the articulation of all knowledge fields and the production of general understandings on social life. For that purpose, complexity must be considered as a basic scientific assumption: it refuses classical scientific method, which is inspired by the reducement of the study object and the understanding that reality is made of linear causality relations between the smallest possible pieces of a phenomenon. The challenges treated in this paper requires a new role to researchers and universities.